Research on the Impact of Marketing Strategy on Consumers’ Impulsive Purchase Behavior in Livestreaming E-commerce - Chen, Bing; Wang, Lei; Rasool, Hassan; Wang, Jun (Frontiers in Psychology, 2022)
Livestreaming e-commerce has emerged as a highly profitable e-commerce that has revolutionized the retail industry, especially during the COVID-19 pandemic. However, research on livestreaming e-commerce is still in its infancy. This study sheds new light on impulsive purchase behavior in livestreaming e-commerce. Based on stimulus-organism-response (SOR) theory, this study introduces the “People-Product-Place” marketing strategy for livestreaming e-commerce from the perspective of consumer perception and aims to understand the impact of marketing strategy on impulsive purchase behavior in e-commerce livestreaming shopping scenes, and to examine the mediating effect of involvement. The study conducted SEM analysis, in Amos, on 437 response sets from an online anonymous survey. The results show that perceived e-commerce anchor attributes, perceived scarcity, and immersion positively influence impulsive purchase behavior; that “People-Product-Place” marketing strategy is important; and that effective marketing triggers impulsive purchase. Perceived e-commerce anchor attributes, perceived scarcity, and immersion positively influence involvement, which positively influences impulsive purchase. Involvement mediates between perceived e-commerce anchor attributes, perceived scarcity and immersion, and impulsive purchase. These findings guide marketers to improve the profitability of livestreaming e-commerce and provide some references of economic recovery for many other countries that also suffered from the impact of the COVID-19 pandemic.